2018
DOI: 10.2196/10141
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of and Interest in Health Apps Among Those With Mental Health Needs: Survey and Focus Group Study

Abstract: BackgroundA large number of health apps are available directly to consumers through app marketplaces. Little information is known, however, about how consumers search for these apps and which factors influence their uptake, adoption, and long-term use.ObjectiveThe aim of this study was to understand what people look for when they search for health apps and the aspects and features of those apps that consumers find appealing.MethodsParticipants were recruited from Northwestern University’s Center for Behavioral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
115
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 30 publications
19
115
0
1
Order By: Relevance
“…The proportion of reviews containing positive and negative sentiments was similar to previous results in both general and mHealth apps whereby the majority of reviews contained positive sentiment [ 21 , 35 ]. The central positive features of engagement consisted of accessibility and personalization/customization of app content, which are in line with previous findings of user reviews [ 30 , 35 , 36 , 49 ]. The main content of negative reviews in this study also supports previous findings, which cite functionality issues, lack of features, and crashing/data loss as the most common complaints [ 16 , 21 , 24 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The proportion of reviews containing positive and negative sentiments was similar to previous results in both general and mHealth apps whereby the majority of reviews contained positive sentiment [ 21 , 35 ]. The central positive features of engagement consisted of accessibility and personalization/customization of app content, which are in line with previous findings of user reviews [ 30 , 35 , 36 , 49 ]. The main content of negative reviews in this study also supports previous findings, which cite functionality issues, lack of features, and crashing/data loss as the most common complaints [ 16 , 21 , 24 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is also crucial that young people are not set up to fail through poorly designed health apps or engagement with well-designed but ineffective digital treatments. Although small-scale qualitative studies have explored young people’s views of mental health apps [ 30 ], more extensive research is needed to understand the nuances of user engagement. Written user reviews on mobile app stores contain a wealth of information about user experience and expectations and are a potentially untapped source of information in research, despite being used by smartphone owners to consider whether to download and engage with a given app [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most consumers find mental health apps through social media, web searches or word of mouth rather than by professional recommendation (Schueller et al 2018). Smartphone owners often rely on online app reviews but these can be misleading.…”
Section: Selection Of Mental Health Appsmentioning
confidence: 99%
“…Moreover, marketing through social media and search engines might be a particularly viable method for dissemination of mobile applications given a recent study which indicated that individuals searched for apps primarily through social media (45.1%), followed by search engines (42.7%; Schueller, Neary, O'Loughlin, & Adkins, 2018). This could be a viable avenue for integrating technology tools (e.g., telehealth for follow-up appointments, mood trackers, self-help apps to review education and practice coping skills until next appointment) for those patients who have low access to mental health services.…”
Section: Promoting Reach and Disseminationmentioning
confidence: 99%
“…Similarly, Latinx (38%) and African-American (43%) adults were more likely than White (32%) adults to use Instagram. Moreover, marketing through social media and search engines might be a particularly viable method for dissemination of mobile applications given a recent study which indicated that individuals searched for apps primarily through social media (45.1%), followed by search engines (42.7%; Schueller, Neary, O'Loughlin, & Adkins, 2018). Recommendation by a family member or friend (36.9%) and provider referral (24.6%) were also found to influence an individual's decision to search for a particular mobile application.…”
Section: Promoting Reach and Disseminationmentioning
confidence: 99%